Rehabilitation Exercises and Their Effect on Agility and Special Speed for Soccer Players with lateral collateral ligament Sprain - jowad, tamara; Salem, Ismaeel (Journal of Physical Education, 2023)
Injuries are considered one of the major obstacles for preforming physical activity in all sports. In soccer, all parts of the player’s body are prone to injury yet statistics show that knee joint is the most commonly injuries joint. Through observing previous studies, the researchers noticed that soccer players get injured a lot thus the research aim at designing rehabilitation exercises and identifying their effect on agility and special speed in soccer players with knee joint ligaments sprain. The researchers used the experimental method on (5) players with mild ligaments sprain. The rehabilitation program was applied for three weeks (20) days. The data was collected and treated using proper statistical operations to conclude that speed and agility significantly developed due to the rehabilitation program.